Front Cover: Investigation of the Reaction Pathways of Biomass‐Derived Oxygenate Conversion into Monoalcohols in Supercritical Methanol with CuMgAl‐Mixed‐Metal Oxide (ChemSusChem 23/2018). Issue 23 (30th November 2018) - Galebach, Peter H.; Thompson, Sean; Wittrig, Ashley M.; Buchanan, J. Scott; Huber, George W.
Abstract : The Front Cover shows the chemical intermediates and final products for the catalytic conversion of wood into C2 –C6 alcohols over a CuMgAl oxide catalyst in methanol. In their Full Paper, P. H. Galebach et al. elucidate the pathway and measure the reaction rate of the key reactions that produce the alcohols. The solubilized wood components are converted into diols in methanol. C−C scission between vicinal diols produces the alcohols which do not further react. Larger diols are produced by C−C methylation coupling reactions between methanol and diols. The rate of the C−C coupling reactions is greater than the rate of C−C scission reactions. Hydrogen for this process is produced from reforming of the methanol. More information can be found in the Full Paper by P. H. Galebach et al. onpage 4007 in Issue 23, 2018 (DOI:10.1002/cssc.201801816 ).